Risk factors of perioperative morbimortality after laparoscopic sleeve gastrectomy: a club coelio multicenter study. Issue 2 (4th March 2018) - Tulelli, B.; Loi, P.; van Vyve, E.; Johanet, H.; Fromont, G.; Dabrowski, A.; Piquart, A.; Delaunay, T.; Ledaguenel, P.; Navez, B.; Maisonnette, F.; Lepere, M.; et al.
Abstract: Objectives: Postoperative complications after Laparoscopic sleeve gastrectomy (LSG) can dramatically compromise patient's outcome. The aim of this study is to analyze the per- and postoperative short-term outcomes after LSG and to assess predictive risk factors of complications. Methods: The study group consisted of 790 patients (610 women and 180 men) who underwent LSG In 2014. All interventions were performed by 18 experienced surgeons members of the Club Coelio. Data about preoperative work-up, surgical techniques, 30-days postoperative morbidity and mortality were collected. Endpoints were perioperative morbidity and mortality and assessment of potential risk factors for complications. Results: Mean age and body mass index were respectively 39 years and 41.5kg/m 2 . Ninety-one patients (11.5%) had previous bariatric surgery. Morbidity rate was 4.7% (37/790) including 16 leaks (2.0%) and 9 bleedings (1.1%) and no deaths. Risk factors for leak were: previous adjustable banding ( p  = .0051), with no difference between removal of the banding and LSG in 1 or 2 steps, and type of endostapler ( p  = .0129). Conclusions: Leakage after Sleeve was rare but still observed even in experienced hands. The leak rate is particularly high when LSG is performed after adjustable gastric banding removal.